Characterization of Antimicrobial Compound Produced from Hericium erinaceus Combating Campylobacter jejuni NCTC11168 - Hamdy, Basma; Yosri, Mohamed; Abed, Nermin; El Kareem, Sayed A.; Ellithy, Amal; Sidkey, Nagwa (Anti-Infective Agents, 2021)
Background: Campylobacter jejuni is the most common cause of enteric infections, particularly among children, resulting in severe diarrhea. Increasing drug resistance of this bacterium against standard antibiotics favors investigations into additional anti-Campylobacter medications that are already used to overcome effects on enteric infections. Methods: Anti-bacterial activity using well diffusion assay of seventeen fungal extracts was tested against C. jejuni NCTC11168. The obtained results of antibacterial screening showed that different tested fungal isolates have different antimicrobial activities, where Hericium erinaceus extract was the highest activity against the tested bacterium. Results: Fractionation pattern has been done by column chromatography. Furthermore, purity was estimated by thin layer chromatography (TLC). Minimal inhibitory concertation (MIC) for the purified compound was 7.81μg/ml. Cytotoxicity for the purified compound was evaluated to be 170μg/ml. 1HNMR, IR and GC-Mass were performed for illustration of the suggested structure of the bioactive compound purified from H. erinaceus. Conclusion: The data presented here suggested that H. erinaceus could potentially be used in modern applications aimed at the treatment or prevention of Campylobacter jejuni infection.
Keywords: Antibacterial activity